Melodic multi-feature paradigm reveals auditory profiles in music-sound encoding - Tervaniemi, Mari; Huotilainen, Minna; Brattico, Elvira (Frontiers in Human Neuroscience, 2014)
Musical expertise modulates preattentive neural sound discrimination. However, this evidence up to great extent originates from paradigms using very simple stimulation. Here we use a novel melody paradigm (revealing the auditory profile for six sound parameters in parallel) to compare memory-related MMN and attention-related P3a responses recorded from non-musicians and Finnish Folk musicians. MMN emerged in both groups of participants for all sound changes (except for rhythmic changes in non-musicians). In Folk musicians, the MMN was enlarged for mistuned sounds when compared with non-musicians. This is taken to reflect their familiarity with pitch information which is in key position in Finnish folk music when compared with e.g., rhythmic information. The MMN was followed by P3a after timbre changes, rhythm changes, and melody transposition. The MMN and P3a topographies differentiated the groups for all sound changes. Thus, the melody paradigm offers a fast and cost-effective means for determining the auditory profile for music-sound encoding and also, importantly, for probing the effects of musical expertise on it.